Auxin efflux controls orderly nucellar degeneration and expansion of the female gametophyte in Arabidopsis. Issue 6 (18th January 2021) - Wang, Junzhe; Guo, Xiaolong; Xiao, Qiang; Zhu, Jianchu; Cheung, Alice Y.; Yuan, Li; Vierling, Elizabeth; Xu, Shengbao
Summary: The nucellus tissue in flowering plants provides nutrition for the development of the female gametophyte (FG) and young embryo. The nucellus degenerates as the FG develops, but the mechanism controlling the coupled process of nucellar degeneration and FG expansion remains largely unknown. The degeneration process of the nucellus and spatiotemporal auxin distribution in the developing ovule before fertilization were investigated in Arabidopsis thaliana . Nucellar degeneration before fertilization occurs through vacuolar cell death and in an ordered degeneration fashion. This sequential nucellar degeneration is controlled by the signalling molecule auxin. Auxin efflux plays the core role in precisely controlling the spatiotemporal pattern of auxin distribution in the nucellus surrounding the FG. The auxin efflux carrier PIN1 transports maternal auxin into the nucellus while PIN3/PIN4/PIN7 further delivers auxin to degenerating nucellar cells and concurrently controls FG central vacuole expansion. Notably, auxin concentration and auxin efflux are controlled by the maternal tissues, acting as a key communication from maternal to filial tissue.